The Influence of Store Atmosphere Mediated by Positive Emotion on Impulse Buying - Putri Dwi Fazrin; Salim Siregar (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2021)
Based on the SPR (Stimulus-Process-Response) model, the store atmosphere can act as a stimulus that someone will process. One of them is a positive emotion that can produce a response in the form of impulse buying. Based on Karawang Central Statistics Agency, there is a change in people’s behavior, seen by the increase in average consumption per year. Merche Karawang Central Plaza makes good use of the phenomenon by creating a stimulus through the store atmosphere that can affect the positive emotion of consumers to impulse buying. This research aims to know, analyze, and explain the influence of store atmosphere on positive emotion, the influence of positive emotion on impulse buying, and the influence of store atmosphere on impulse buying at Merche Karawang Central Plaza Store. The method is quantitative, with the transaction in Merche Karawang Central Plaza store over the past year as the population and 116 respondents through the sloven’s formula, the research uses a technical path analysis. This result is store atmosphere influences positive emotions. Also, positive emotion influences impulse buying, and the store atmosphere influences impulse buying. Positive emotion does not mediate the relationship between store atmosphere and impulse buying.